Ultrahigh-strength low carbon steel obtained from the martensitic state via high pressure torsion - Mueller, T.; Kapp, M. W.; Bachmaier, A.; Felfer, Peter; Pippan, R. (Acta Materialia, 2019)
A new ultrahigh-strength structure is created by severe plastic deformation of a martensitic 0.1 wt.-% C steel using high pressure torsion (HPT) at room temperature. Tensile tests reveal an ultimate tensile strength of 2.4 +/- 0.1 GPa after an equivalent strain of epsilon(vM) = 7.5 - to our knowledge the highest tensile strength ever reported for a carbon steel with such low carbon content. During HPT, a lamellar microstructure is formed with decreasing lamellar spacing for increasing plastic strain. Micropillar compression tests give crucial insights into the mechanical properties, which are correlated to the deformation behavior of this material. Strong similarities compared to HPT-treated pearlitic steel are found in spite of the large differences concerning both carbon content and phase composition. The possibilities and limits of strength maximization in carbon steels are evaluated and discussed. (C) 2018 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-03-06